Pengaruh Literasi Keuangan, Pendapatan, dan Self Control terhadap Financial Management Behavior pada Mahasiswa. - Septiarum, Ade Fitriani Kusuma; Susanti, Susanti (Jurnal Pendidikan Akuntansi (JPAK), 2024)
Financial management is a skill that students should have in their lives. As result, students should have an income, attend finance classes at uniersity be able to balance income and spending comprehend the many sorts of financial activities practice self-control over financial expenditures and be able to manage personal money. The goal of this study is to examine the impact of financial literacy income, and self-control on student financial management behaior. This is a associative quantitative study. Measurement of variables through a Likert scale. The population studied was the 2018 and 2019 Accounting Education Study Program students, totaling 117 students. The number of samples was determined using the Slovin formula for 91 students. The sampling approach employing the Non-Probability Sampling technique in conjunction with the Purposive Sampling technique. Techniques for collecting data using online surveys. This study report concludes that financial literacy, income, and self-control all have a substantial effect on students' money management behavior.